Smart optimization of PV panel output using Fuzzy Logic Controller based solar tracker - Marhani Rosyadah; RD Kusumanto; Tresna Dewi (SINERGI, 2022)
Currently, more people choose renewable energy over conventional energy, such as solar energy, which is the most eligible renewable energy in Palembang and South Sumatra due to its strategic location in the equator. However, solar energy cultivation is experiencing various obstacles resulting in not producing maximum output, which is indicated by low output efficiency. Solar tracker or solar tracking system is one of the best methods to ensure the maximum sunlight received by the PV panels. This paper shows the effectiveness of a solar tracking system controlled by FLC compared to a fixed system. The data is taken for 15 days during the weather changing in Indonesia, from the rainy season to the dry season. The maximum power generated by dual-axis solar tracking and fixed solar panels is 96.4768 W and 63,5106 W, whereas the power generated by dual-axis solar tracking is 32.9662 W higher than fixed solar panels. The highest efficiency obtained by dual-axis solar tracking is 25%, while fixed solar panels are 16%. The application of dual-axis solar tracking can optimize and increase the efficiency of solar panels because the panels are always perpendicular to the position of the highest irradiance. Data results show that FLC-based solar effectively improves power output and efficiency compared to a fixed solar panel.